2018
DOI: 10.1182/bloodadvances.2017012500
|View full text |Cite
|
Sign up to set email alerts
|

Toward dual hematopoietic stem-cell transplantation and solid-organ transplantation for sickle-cell disease

Abstract: Sickle-cell disease (SCD) leads to recurrent vaso-occlusive crises, chronic end-organ damage, and resultant physical, psychological, and social disabilities. Although hematopoietic stem-cell transplantation (HSCT) is potentially curative for SCD, this procedure is associated with well-recognized morbidity and mortality and thus is ideally offered only to patients at high risk of significant complications. However, it is difficult to identify patients at high risk before significant complications have occurred,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…SCT is likewise associated with the risk of graft versus host disease, as well as hepatic veno-oclusive disease [ 37 ]. Dual SCT/OLT has been described in other disease processes, and may be an avenue explored in SCD patients in the coming years [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCT is likewise associated with the risk of graft versus host disease, as well as hepatic veno-oclusive disease [ 37 ]. Dual SCT/OLT has been described in other disease processes, and may be an avenue explored in SCD patients in the coming years [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell disease (SCD) is the most common hemoglobinopathy, and there are approximately 100,000 patients in the United States with the disease [ 1 , 2 ]. This results in a major impact on healthcare, with between 68 and 75,000 hospitalizations a year, and approximately 100,000 emergency department visits, with an estimated total cost of care of $2.4 billion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some rarer serious complications involve specific groups of patients, such as children [ 4 , 5 , 6 ]. Recipients of dual transplantations might be an even greater challenge for doctors [ 7 , 8 ]. Those challenges indicate that there is an immense demand for progress in the field of transplantology [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Africa possesses the major affected patients estimated to be about 50 millions [3,4]. Nowadays, bone marrow transplant, also known as stem cell transplant, is mostly considered as potential cure for sickle cell anemia [8][9][10][11][12][13]. Stem cell transplant from a compatible donor was found more recently to be successful for sicklers patients becoming SCD-free after treatment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%